2016
DOI: 10.1021/acssensors.6b00266
|View full text |Cite
|
Sign up to set email alerts
|

Fast Electrochemical miRNAs Determination in Cancer Cells and Tumor Tissues with Antibody-Functionalized Magnetic Microcarriers

Abstract: Microribonucleic acids (miRNAs) have been linked with various regulatory functions and diseases and constitute important targets in future medical diagnostics and prognostics. We report here a novel sensitive and rapid bioelectrochemical strategy for miRNA determination. This strategy involves the development of a sensing approach making use of magnetic beads (MBs) modified with a specific DNA-RNA antibody as capture bioreceptor and amperometric detection implying the H2O2/hydroquinone (HQ) system at disposabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 33 publications
6
36
0
1
Order By: Relevance
“…Three miRNAs, miR‐21, let‐7a and miR‐31, associated with development and progression of cervical cancer in women , were selected as target miRNAs. The results obtained, after a suitable optimization of the methodology, showed that the new HCR‐based immunosensing strategy offers in a short assay time (120 min) a sensitivity 17 and 131 times higher than that previously reported using individually modified MBs with the same capture antibody without amplification or a HCR strategy implemented on the surface of MBs , respectively. The electrochemical platform was successfully employed for the simultaneous determination of three target miRNAs in RNA t extracted from various cancer cell lines and from cervical precancerous lesions of women suffering from the most severe grade of high‐grade squamous intraepithelial lesion (HSIL).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Three miRNAs, miR‐21, let‐7a and miR‐31, associated with development and progression of cervical cancer in women , were selected as target miRNAs. The results obtained, after a suitable optimization of the methodology, showed that the new HCR‐based immunosensing strategy offers in a short assay time (120 min) a sensitivity 17 and 131 times higher than that previously reported using individually modified MBs with the same capture antibody without amplification or a HCR strategy implemented on the surface of MBs , respectively. The electrochemical platform was successfully employed for the simultaneous determination of three target miRNAs in RNA t extracted from various cancer cell lines and from cervical precancerous lesions of women suffering from the most severe grade of high‐grade squamous intraepithelial lesion (HSIL).…”
Section: Introductionmentioning
confidence: 77%
“…With the aim of overcoming some of these limitations, attractive EC biosensors have recently been proposed for the determination of miRNAs using novel bioreceptors such as tombusvirus protein p19, with a high affinity for the determination of RNA‐RNA homohybrids of limited length or commercial antibodies with a high affinity for RNA‐DNA heteroduplexes of any length . Moreover, to minimize the disadvantages of conventional amplification strategies, the use of an isothermal amplification known as hybridization chain reaction (HCR) has recently been proposed for the determination of miRNAs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach involved the use of ProtG-MMPs modified with the antibody AbS9.6 specific for the DNA/RNA heteroduplexes as selective microcarriers to capture the hybrids previously formed in solution by homogeneous hybridization between the biotinylated complementary DNA probe and the target miRNA [45]. This immunosensing approach exhibited a dynamic range from 8.2 to 250 pM and a LOD of 2.4 pM (60 amol) of the synthetic target miRNA.…”
Section: Micromagnetic Particlesmentioning
confidence: 99%
“…Within this context, the main characteristics of novel biosensing scaffolds for the determination of cancer related-miRNAs [1][2][3] and autoantibodies [4] against tumor associated antigens (TAAs), relevant biomarkers considered for both early diagnosis and prognosis, will be presented. The developed methodologies, based on the coupling of attractive bioreceptors and bioassay formats, functionalized magnetic microcarriers, and electrochemical detection at disposable transducers, have demonstrated practical applicability for the accurate determination of the endogenous concentration of the target analytes in solid (fresh and FFPE breast human tissues) and liquid (human serum from colorectal and ovarian cancer patients) biopsies.…”
mentioning
confidence: 99%